Quel français pour les étudiants de la faculté de droit de l'Université du Cap? - Muzodi, Kenda Henry (French Language and Literature, 2017)
Over the years, the University of Cape Town (UCT) has been and is still offering French language, through its French Section. Those enrolling in the named French language programme are undergraduate students of different faculties of the University of Cape Town including the faculty of law. The variety of French that these students acquire is the variety known as general French. This study analyses the law students' needs in French language. A questionnaire and interviews were used to collect data about students' needs, objectives and expectations. The conclusion can be drawn that the University of Cape Town law students needs are to work for international organizations of Human Rights and that they need some linguistic skills not only in general French but also the mastery of French referred to the professional discipline known as French for specific purposes.